Scoping review: Influence of cisgender male and female genders on health literacy of the elderly people. (13th October 2021) - Felix, Mark Stephan; Kitcharoen, Patreeya; Le, Thi Ngoc Phuc; Wei, Min; Puspitasari, Dewi Cahyani; Guo, Haihu; Jin, Weiyun
Abstract: This scoping review mapped out the relevant literature, identified gaps and made suggestions on the influence of cisgender on the health literacy (HL) of the elderly people. This scoping review was guided by the PRISMA‐ScR checklist. The databases Wiley Online Library™ and Elsevier™ were searched for academic articles published in the English language between February 2011 and February 2021 that met a pre‐set criteria of content. The process of selection of sources of evidence based on screening and eligibility of evidence reduced the initially identified 153 sources of evidence in the searched databases to 14 sources of evidence. The content of these 14 sources of evidence was mapped out on a charting table where data was summarised and synthesised individually and collectively by the authors. Repetitive and irrelevant data were deleted. Identified gaps include the lack of extensive exploration of male and female genders alone as a determinant of HL, how gender may be utilised to encourage elderly men and women to apply HL, how different sociocultural and sociodemographic backgrounds of elderly men and women would require separate academic research, the scarcity of social sciences based research and qualitative research methodologies on the subject as well as the use of mixed‐methodologies and longitudinal studies. Future research directions were suggested and limitations of this scoping review are addressed in the discussion.